How Fast Are the Asian Countries Progressing Toward Green Economy? Implications for Public Health - Shao, Ming; Jin, Hui; Tsai, Fu-Sheng; Jakovljevic, Mihajlo (Frontiers in Public Health, 2022)
Monitoring progress towards green economy has been a key policy focus globally. The purpose of our study is to assess Asian countries’ green development performance, as well as the progress towards green economy over time. To achieve this goal, we propose a Green Development Index (GDI) to assess the level and ranking of green development for Asian countries, and then we measure the progress towards green economy by the method based on the compound annual growth rate (CAGR). The result shows that the northeast Asian countries together with the Singapore and Israel are leaders in green development performance across Asia, but the most progress towards green economy has been achieved by some medium green development level countries, like China. And the countries with the fastest movement away from green economy are some laggard countries with poor green development performance, such as Syria and Yemen. More generally, the leading countries have reached a high green development level, and the medium ones move fast toward green economy, while some laggards get worse.